The Author’s Worldview in the Novel Teruslah Bodoh Jangan Pintar by Tere Liye - Nuzulia, Hilda; Supriyanto, R.M. Teguh (International Journal of Language Teaching and Education, 2026)
This research aims to describe the author's worldview in the novel "Teruslah Bodoh Jangan Pintar" by Tere Liye, particularly as reflected in the themes, characters, plot, and conflicts, based on Lucien Goldmann's theory of genetic structuralism. This study employs a qualitative approach, specifically literary sociology. The data obtained consist of words, phrases, quotations, and sentences that are interrelated with the author's worldview. Data were collected using observation and note-taking methods, and analyzed using Lucien Goldmann's dialectical method. The results of the study explain the author's worldview, which is realized through the themes, characters, plot, and conflicts. This worldview is used to express various ideologies, ideas, values of life, and criticisms of the realities of life within the scope of society. Several phrases used in the novel require attention to the politeness culture that has been reflected in Indonesian society. Furthermore, this research proves that the use of sarcasm in the novel "Teruslah Bodoh Jangan Pintar" by Tere Liye can influence readers' understanding of the meanings conveyed in the novel, both explicitly and implicitly.